Pandangan Islam Atas Teori Keunggulan Mutlak Dan Teori Keunggulan Komparatif - Mulyana, Rijal Assidiq (Holistik: Journal for Islamic Social Sciences, 2023)
In classical economics, two theories are known: the theory of absolute advantage and the theory of comparative advantage. Both theories are part of the concept of international trade in the classical era. The theory of absolute advantage was proposed by Adam Smith, while the theory of comparative advantage was developed by David Ricardo. Research aims to explain the Islamic perspective on these two theories of international trade within the classical school of thought. The findings of the research show that Islam allows trade, including trade conducted using the approaches of both theories, which is confirmed by verses from the Quran. However, in Islam, trade is not only understood as an effort to gain profit or prosperity but also as an act of worship. Therefore, in Islam, every trade is regulated and governed by Sharia law, while emphasizing morals and ethics. In the theory of absolute advantage, Islam reinforces the utilization of natural resources to produce products with absolute advantage. In the theory of comparative advantage, Islam emphasizes the acquisition of technology that must be possessed by human resources. This implies that in Islam, trade is not only oriented towards achieving worldly happiness but also eternal happiness in the hereafter